2013
DOI: 10.1017/s1471068413000100
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of semantic rule updates based onSE-models

Abstract: Logic programs under the stable model semantics, or answer-set programs, provide an expressive rule-based knowledge representation framework, featuring a formal, declarative and well-understood semantics. However, handling the evolution of rule bases is still a largely open problem. The AGM framework for belief change was shown to give inappropriate results when directly applied to logic programs under a non-monotonic semantics such as the stable models. The approaches to address this issue, developed so far, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
(100 reference statements)
0
24
0
1
Order By: Relevance
“…As to the case of update of logic programs Slota and Leite (2013) argued that semantic rule updates based on SE models seem to be inappropriate. Indeed they showed that in presence of the irrelevance-of-syntax postulate (whose counterpart in the context of revision is (RA4)), semantic rule update operators based on SE models violate some reasonable properties for rule updates, i.e., dynamic support and fact update (see (Slota and Leite 2013) for more details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the case of update of logic programs Slota and Leite (2013) argued that semantic rule updates based on SE models seem to be inappropriate. Indeed they showed that in presence of the irrelevance-of-syntax postulate (whose counterpart in the context of revision is (RA4)), semantic rule update operators based on SE models violate some reasonable properties for rule updates, i.e., dynamic support and fact update (see (Slota and Leite 2013) for more details).…”
Section: Resultsmentioning
confidence: 99%
“…As to the case of update of logic programs Slota and Leite (2013) argued that semantic rule updates based on SE models seem to be inappropriate. Indeed they showed that in presence of the irrelevance-of-syntax postulate (whose counterpart in the context of revision is (RA4)), semantic rule update operators based on SE models violate some reasonable properties for rule updates, i.e., dynamic support and fact update (see (Slota and Leite 2013) for more details). The property of dynamic support can be expressed unformally as follows: an rule update operator ⊕ satisfies dynamic support if every atom true in an answer set from any updated program P ⊕ Q should be supported by a rule in P ∪ Q, i.e., it should have some "justification" in either the original program or the new one.…”
Section: Resultsmentioning
confidence: 99%
“…While these two programs again share the same set of SE models, they too should not be interchangeable, since after a removal of the rule a., b should not be derived from the latter program any more. This property has become known as support [Slota and Leite 2013]. To address these two issues, Inoue and Sakama [2004] introduced a new notion of program equivalence that is stricter than strong equivalence, called C-update equivalence: any two programs P 1 ,…”
Section: Related Workmentioning
confidence: 99%
“…Such relationships are expressed on the rule-level, by the individual rules contained in a program. By neglecting information expressed on the rule-level, the distance-based approach fails to satisfy the property of preservation [Inoue and Sakama 2004] and the property of support [Inoue and Sakama 2004;Slota and Leite 2013]. This leads to some highly unintuitive results, as illustrated by the following two examples.…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue open for future work is a more finegrained characterization of updating bridge rules (and knowledge bases) as studied in [14] in light of the encountered difficulties when updating rules [24,25,27] and the combination of updates over various formalisms [25,26].…”
Section: Related and Future Workmentioning
confidence: 99%